2018
DOI: 10.1088/1361-6528/aae148
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of GaAsSb/AlGaAs nanowire ensemble Schottky barrier based photodetector via in situ annealing

Abstract: In this work, we report on the p-i GaAsSb/AlGaAs nanowires (NWs) ensemble device exhibiting good spectral response up to 1.1 μm with a high responsivity of 311 A W, an external quantum efficiency of 6.1 × 10%, and a detectivity of 1.9 × 10 Jones at 633 nm. The high responsivity of the NWs has been attributed to in situ post-growth annealing of GaAsSb axial NWs in the ultra-high vacuum. The enabling growth technology is molecular beam epitaxy for the Ga-assisted epitaxial growth of these NWs on Si (111) substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…There are already reports that describe detailed characterizations and investigation of the optical properties of GaAsSb NWs on Si substrates grown via CVD [78] and MBE. [27][28][29]52,[79][80][81][82][83][84][85][86] As mentioned earlier, the Sb content, for structures grown on Si, is kept at a relatively low level. In several cases of growth on patterned Si substrates, where VLS growth occurred, the size of the pattern plays an important role in the morphology and elemental composition of the structures.…”
Section: 13) Gaassb Nanowiresmentioning
confidence: 99%
See 2 more Smart Citations
“…There are already reports that describe detailed characterizations and investigation of the optical properties of GaAsSb NWs on Si substrates grown via CVD [78] and MBE. [27][28][29]52,[79][80][81][82][83][84][85][86] As mentioned earlier, the Sb content, for structures grown on Si, is kept at a relatively low level. In several cases of growth on patterned Si substrates, where VLS growth occurred, the size of the pattern plays an important role in the morphology and elemental composition of the structures.…”
Section: 13) Gaassb Nanowiresmentioning
confidence: 99%
“…[84] To further improve surface passivation, core/shell structures can be grown, where AlGaAs has been used as shells to neutralize surface states. [28] for most of the papers mentioned so far, rendering the NWs Sb-poor. [27][28]79,[83][84][85] However, the significance of high wavelength emission for telecommunication applications and infrared light detections leads to concentrated efforts to increase the amount of Sb that is incorporated in the NWs.…”
Section: 13) Gaassb Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the III-V materials, GaAsSb nanowires are particularly attractive due to their wide tunability of band gap within the 870-1700 nm (1.425-0.73 eV) regime of the electromagnetic spectrum and large carrier mobility (see ref. 10 and references therein). In addition, antimonide NW's have a relatively large exciton Bohr radius below which one anticipates quantum confinement compared to other III-V semiconductors.…”
mentioning
confidence: 99%
“…In an axial configuration, these nanowires exhibit a pure zinc blende crystal structure with a reduced density of planar defects. The high structural and optical quality of GaAsSb axial nanowires has led to promising photodetectors 10,11 and subwavelength wire lasers 12 in the near-IR telecommunications wavelength range and high current density tunnel diodes 13 . Ganjipour, et al 14 fabricated a single hole transistor from a p-type GaSb nanowire and suggested that their results are relevant for spintronic applications and quantum information science since hole confinement in quantum systems can enhance the spin relaxation time.…”
mentioning
confidence: 99%